Asymmetric transfer hydrogenation of α-amino β-keto ester hydrochlorides through dynamic kinetic resolution1. Issue 70 (31st July 2015) - Echeverria, Pierre-Georges; Cornil, Johan; Férard, Charlène; Guérinot, Amandine; Cossy, Janine; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie
<x xml:space="preserve">Abstract</x> The development of Ru-catalyzed asymmetric transfer hydrogenation of α-amino β-keto ester hydrochlorides is described.